Penanggulangan COVID-19 Tingkat Lokal Melalui Kebijakan Adaptasi Kebiasaan Baru (AKB) di Provinsi Jawa Barat - Dian Herdiana (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
The West Java Provincial Government issued a New Life Adaptation (AKB) policy in response to the implementation of a ‘new normal’ that will be implemented in the cities and districts among West Java Province. Conceptually this AKB policy needs to be assessed whether the substance is in line with the guidelines from the World Health Organization (WHO) and the Government or is a new and different concept? Empirically what issues and opportunities arise when the AKB policy is implemented?. This research uses a qualitative approach with descriptive methods, data collection is taken from secondary sources in the form of government reports, books, journals and other relevant sources. The results revealed that the AKB policy was substantially the adoption of the the new normal guidelines from the World Health Organization (WHO) and the Government. The issue that arises empirically is how the implementation of the AKB policy can minimize the spread of COVID-19 in line with the sustainability of community activities. Efforts to be made by the West Java Provincial Government in the future are to synergize AKB policy at the provincial level with AKB policy at the city and district level, as well as educating and disseminating information about COVID-9 and AKB Policy to the public.